When state capacity dissolves: Explaining variation in violent conflict and conflict moderation. (6th April 2017) - Gledhill, John
Abstract: When state capacity dissolves, we ordinarily assume that violent conflict will break out, and then spiral towards a high degree of intensity. However, this is not always the case. Rather, on occasion, states suffer a sharp and severe loss of capacity, but little or no collective violence follows. And, on other occasions, violent conflict erupts, but that conflict does not escalate into civil war; rather, it plateaus, and then recedes. This article offers an analytic framework for explaining such variation in the presence, absence, and intensity of violent conflict following a dissolution of state capacity. I argue that the strength of state and societal organs prior to a loss of state capacity shapes the broad trajectory of violence after such a loss. In making that claim, I associate three state-society dynamics before state dissolution with three levels of violent conflict, post-dissolution. Drawing on multi-country fieldwork, I illustrate the proposed framework by presenting three diverse cases of dissolving state capacity and conflict: Georgia (1991–3); Albania (1991–2); and Yemen (2011–13).